Bandgap-engineered ferroelectric single-crystalline NBT-BT based nanocomposites with excellent visible light-ultrasound catalytic performance. (November 2022) - Xiao, Hongyuan; He, Jiahuan; Lu, Xunyu; Wang, Feifei; Guo, Yiping
Abstract: Bandgap engineered ferroelectrics exhibit encouraging multi-energy catalytic performance by coupling the piezoelectricity and photoexcitation, which shows immense potential for environmental remediation and fuel production. However, it is challenging to prepare nano single-crystalline ferroelectric piezo-photoelectric with strong visible light absorption ability. Here, Ni mediated NBT-BT(NBT-BNT) single-crystalline nanocubes around 100 nm with considerable visible light absorption were synthesized by a high-temperature hydrothermal method. The mechanism of Ni2+ on the formation of NBT-BT nanocubes was proposed. The catalytic efficiency of NBT-BNT nanocubes is enhanced by decorating carbon quantum dots (CQDs). The RhB can be degraded within 8 min and the hydrogen production rate reaches up to ∼350 μmol g-1h-1 under visible light-ultrasonic condition. Moreover, under the simulated sunlight-ultrasound condition, RhB can be degraded within merely 3 min and a high H2 production rate of ∼747 μmol g-1h-1 is achieved. This work presents a paradigm for preparing ferroelectric single-crystalline nanocatalysts for multi-energy catalytic application. Graphical abstract: Image 1 Highlights: NBT-BT based single-crystalline nanocubes have been synthesized for the first time. Doping Ni into NBT-BT realizes absorption of visible/NIR and morphology modulation. Decorating CQDs to NBT-BNT improves the light-ultrasound catalytic performance. Propose the mechanism of Ni ion-induced single-crystalline nanocube formation. NBT-BNT@CQDs can degrade RhB within 3 min and H2 production rate is 747 μmolg-1h-1.